(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The present article aims to analyze the role played by the Brazilian Federal Supreme Court (STF) in decisions related to the COVID-19 pandemic containment measures adopted by the Federal Executive Branch. The analysis seeks to determine whether the Court, when issuing these decisions, exceeded the limits of its constitutional competences, engaging in judicial activism, or simply applied constitutional norms. To clarify this issue, the following legal actions will be examined: Direct Actions of Unconstitutionality (ADIs) - No. 6,341/DF - No. 6,351/DF - No. 6,347/DF - No. 6,353/DF, as well as the Direct Action for the Declaration of Non-Compliance with a Fundamental Precept (ADPF) nº. 672/DF. In conclusion, we will assert that none of the decisions rendered by the Supreme Court demonstrated judicial activism. On the contrary, the Court strictly adhered to the limits imposed by the legal framework, without encroaching upon the spheres of competence of the Legislative and Executive Branches.